2022
DOI: 10.1111/and.14434
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heavy alcohol consumption and cigarette smoking on sperm DNA  integrity

Abstract: The purposes of the presents study were to investigate the impact of alcohol consumption and cigarette smoking on semen parameters and sperm DNA quality, as well as to determine whether tobacco smoking, or alcohol consumption causes more deterioration of sperm quality. Two hundred and eleven semen samples of men were included in this study. Four groups were studied: heavy smokers (N = 48), heavy drinkers (N = 52), non‐smokers (n = 70), and non‐drinkers (n = 41). Semen parameters were determined according to WH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 91 publications
(120 reference statements)
1
13
0
2
Order By: Relevance
“…Although our results are consistent with the previous results showing no negative effects of cigarette smoking on sperm DFI (De Bantel et al, 2014;Sergerie et al, 2000), their study includes normal healthy men and patients with suspected infertility. On the contrary, some research suggests a significant relationship between smoking and sperm DFI (Amor et al, 2022;Choucair et al, 2016;Elshal et al, 2009). Sepaniak et al (2006) reported a significantly higher percentage of sperm DFI in smokers than in non-smokers (Sepaniak et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Although our results are consistent with the previous results showing no negative effects of cigarette smoking on sperm DFI (De Bantel et al, 2014;Sergerie et al, 2000), their study includes normal healthy men and patients with suspected infertility. On the contrary, some research suggests a significant relationship between smoking and sperm DFI (Amor et al, 2022;Choucair et al, 2016;Elshal et al, 2009). Sepaniak et al (2006) reported a significantly higher percentage of sperm DFI in smokers than in non-smokers (Sepaniak et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…This might be because most of our patients were non‐smoker (55%) and did not drink alcohol for 58.3% of them. With regards to alcohol consumption units, this data remains unknown for 14.7% of our patients but we do know that heavy smoking and alcohol abuse are both deleterious for sperm quality 26,27 . Nevertheless, these parameters should be taken into account in an andrology assessment as they induce oxidative stress and DNA damage 28–30 …”
Section: Discussionmentioning
confidence: 96%
“…With regards to alcohol consumption units, this data remains unknown for 14.7% of our patients but we do know that heavy smoking and alcohol abuse are both deleterious for sperm quality. 26,27 Nevertheless, these parameters should be taken into account in an andrology assessment as they induce oxidative stress and DNA damage. [28][29][30] Age was also considered as an important parameter as a metaanalysis showed a trend of a lower sperm concentration with increasing paternal age, due to endocrine disruptors and accumulated oxidative stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, no change was found between the two groups regarding conditions which could affect sDF amount and/or progressive motility, including exposure to toxicant (Irnandi et al, 2021; Recio‐Vega et al, 2008) or high temperature (Garolla et al, 2013), smoking habits (Axelsson et al, 2022; Sharma et al, 2016), alcohol consumption (Amor et al, 2022; Martini et al, 2004), varicocele (Blumer et al, 2008; Pallotti et al, 2018), and recent urogenital infections (Pagliuca et al, 2021; Weidner et al, 2013). The two groups were also similar for age, abstinence, drug consumption, daily sedentary time, and intensity of physical exercise (Table 1), all affecting sperm progressive motility and/or DNA quality as well (Gaskins et al, 2015; Hallak et al, 2020; Lu et al, 2020; Priskorn et al, 2016; Vaughan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%